The Influence of Digital Marketing and Influencers on Interest in Buying Used Cars at CV Trisakti Motor Surabaya - Zain, Muhammad Zaki; Purwanto, Sugeng (International Journal of Economics (IJEC), 2025)
This study aims to analyze the influence of digital marketing and influencers on purchase intention at CV Trisakti Motor showroom in Surabaya, using a quantitative approach. The population of the study consists of TikTok and Instagram users, with a sample of 104 respondents selected through non-probability sampling using convenience sampling techniques. The data were analyzed using descriptive statistics and Partial Least Squares (PLS) with the SmartPLS application. The results indicate that both digital marketing and influencers have a positive and significant effect on purchase intention.